2019
DOI: 10.1111/jcmm.14737
|View full text |Cite
|
Sign up to set email alerts
|

circFBXL5 promotes breast cancer progression by sponging miR‐660

Abstract: Increasing studies have revealed that circular RNAs (circRNAs) play important roles in cancer progression. However, the potential involvement of circRNAs in breast cancer metastasis to lung is not clear so far. In this study, we conducted circular RNA microarrays of primary breast cancer tissues and lung metastatic tissues. The results revealed that circFBXL5 (hsa_circ_0125597) up‐regulated the most in lung metastatic tissues. Survival analysis revealed that high levels of circFBXL5 correlated with worse outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
(29 reference statements)
1
16
0
Order By: Relevance
“…For example, circVAPA regulates cell proliferation and migration by sponging miR‐130a‐5p in breast cancer 26 . CircFBXL5 contributes to the progression of breast cancer by interacting with miR‐660 27 . In the present study, miR‐509‐3p was identified by bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 74%
“…For example, circVAPA regulates cell proliferation and migration by sponging miR‐130a‐5p in breast cancer 26 . CircFBXL5 contributes to the progression of breast cancer by interacting with miR‐660 27 . In the present study, miR‐509‐3p was identified by bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 74%
“…Circular RNAs (circRNAs) are a class of RNAs that have been studied a lot in recent years and have received extensive attention due to their unique covalently closed structure [7]. Many studies have demonstrated that circRNAs can be involved in the proliferation and metastasis of cancer cells to play a pro-cancer or anticancer effect in cancer progressions, such as circFMN2, circFBXL5 and circGRAMD18 [8][9][10]. In OSCC, hsa_ circ_0004491 was found to be lowly expressed in OSCC, and its knockdown could enhance the metastasis ability of OSCC [11].…”
Section: Introductionmentioning
confidence: 99%
“…Of all prognostic studies, one study investigated the prognostic value of tumor‐inhibitory circRNAs on DFS, 40 together with the other study assessed a combination of 10 circRNAs using The Cancer Genome Atlas clinical data for BC, 41 were both eliminated. Finally, 16 articles, 20‐35 including 4 individual studies on the diagnosis and 13 on the prognosis, were included for the subsequent meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Given that circRNAs are insensitive to nucleases and more stable than ordinary linear RNA, they are expected to be new biomarkers for monitoring various cancers 18,19 . And circRNAs are intensively reported to have the potential of the early diagnosis and prognostic prediction of BC as novel molecular biomarkers 20‐35 . However, the appraisals of their efficacy are commonly limited by the small sample size, high bias, and single‐center population of the already reported trials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation